Gong Xi - Raya Faculty of Engineering, 2000 - Universiti Malaysia Sarawak, Faculty of Engineering (Universiti Malaysia Sarawak (UNIMAS), 2000)
Faculty of Engineering had become a host for Gong Xi -Raya 2000. This picture shows staff and student celebrating the events